The French Occupation of Syria and the fall of Damascus and their reflections on Trans-Jordan - AbuSeeni, Dr.Abdalhameed Mohammad; Alzoubi, Dr.Amjad Ahmad (Al-Adab Journal, 2020)
The study investigated the reflections of the fall of the Arabian government administered by Prince Faisal bin Hussein in Damascus and the French occupation of Syria in July 24, 1920. It also investigated the consequences of this occupation on Trans-Jordan (Southeast of Bilad Alsham). Moreover, this study has also discussed the local citizens' reaction towards that occupation and their attempts to organize their local affairs in order to achieve their political pursuits in order to maintain the rest of their country. This study has provided two main themes depending on the possible available Jordanian British documents. The researchers used the descriptive historical approach. The results showed that the residents of Transjordan played a major role in influencing the event mainstream regarding resisting the French occupation project in the north of the Bilad Alsham as well as in the British occupation project in the south. The study recommends that it is necessary to uncover the hidden events regarding the resistance of the residents of the Bilad Alsham especially in the eastern parts towards the French occupation in the area in the first half of the twentieth century.